"Saving" the City: Harland Bartholomew and Administrative Evil in St. Louis. (4th March 2018) - Benton, Mark
Abstract : City planner Harland Bartholomew rose in prominence along with the popularity of scientific city-efficient planning during the early to mid-twentieth century. In the pursuit of solutions to urban problems, Bartholomew concluded that the most efficient way to revitalize St. Louis, Missouri, was through the clearing of slums. In an attempt to solve the city's economic and demographic problems, slum clearance destroyed and displaced Black neighborhoods whose 70, 000 residents were seen as detrimental to the city's success. Bartholomew's planning was in line with the public administration theoretical perspective of administrative evil, which states that technical-rational specialists sometimes commit acts of cruelty without intending to. Through his attempts to revitalize and renew the city, Harland Bartholomew did a great deal of evil to Black populations in St. Louis. This article identifies the ways that Bartholomew's administrative evil was masked and perceived as a moral good despite its displacement of Black residents.